TRAUMA HEALING PADA PEREMPUAN KORBAN PLECEHAN SEKSUAL VERBAL (CATCALLING) - Nani Alaniah Yaya; Nina Fitriyani (Jurnal Doppler, 2023)
Sexual harassment is increasingly prevalent in society by exposing various forms of sexually debilitating acts committed by men against women. The forms of sexual harassment experienced by women are not always in non-verbal forms but also in verbal forms. Verbal harassment is perpetrated by men in public spaces such as on the side of the road or in places where men usually gather. The purpose of this research is to find out "how to trauma heal victims of verbal disappearances (catcalling)". This research is a library research with a qualitative type. Data collection was carried out by tracing primary and secondary sources related to verbally disturbing influences on trauma in young girls. Based on research results, one of the trauma healing therapies that can be done is self-healing because by doing this, individuals can heal independently without having to report or wait for the cases they are experiencing to be resolved so they can recover. The point is that individuals can heal the trauma, anxiety and fear that they experience with the help of themselves without having to take drugs from doctors or seek experts who can help the wound healing process while they can still do it themselves.